Detection of Inhomogeneity After Mixing Solutions by Analyzing the Chemical Wave Pattern in the Belousov-Zhabotinsky Reaction - Okamoto, Yasunao; Okita, Erika; Yamamoto, Daigo; Nakata, Satoshi; Shioi, Akihisa (Frontiers in Physics, 2022)
The correlation between BZ reaction and mixing state has been studied for decades, and the researchers is trying to apply it to chemical engineering. We observed a chemical wave pattern in the Belouzov-Zhabotinsky (BZ) reaction based on the inhomogeneity after mixing BZ and ferroin solutions with a mixing method named the rotation-and-stop method. A one-dimensional chemical wave appeared for large inhomogeneity in mixing. The frequency and wavenumber decreased with decreasing degree of inhomogeneity. In an almost perfectly mixed state, the wavenumber significantly reduced and approached the global oscillation. The degree of mixing could be efficiently determined by this reported method. Perfect mixing has never been realized in natural and biological systems. The results of this study can be applied to estimate the degree of mixing in a solution that is not being stirred after the mixing process.